PENGARUH POLITIK DALAM SISTEM PEMILIHAN KEPALA DAERAH DI INDONESIA - Asmuni - (Unram Law Review, 2017)
The election of regional in Indonesia has not reached the objectives of the General Election as referred to in the Constitution 1945. This is much influenced by political parties, therefore the issue raised is the political influence in the system of regional elections. Based on the results of the discussion that analyzed and drawn conclusions: Political influence in the system of regional election in Indonesia has an important position (status) and role in every democratic system. The Party plays role very strategic liaison between government processes and citizens. Even the political parties that determine democracy, so it is a pillar that important to strengthened its institutionalization In any democratic political system (the degree of institutionalization). A good party system determines the functioning of the state administration system based on the principle of in a broad sense "checks and balances". In contrast, the effective functioning of the state's institutional functions in accordance with the principles of checks and balances under the constitution also greatly determines the quality of party systems and the mechanisms of democracy developed in a country, so that political parties are just one of the forms of institutionalization as a form of expression of ideas , Free thoughts, views, and beliefs in democratic societies and political parties that act as intermediaries in the processes of state decision making, connecting citizens with state institutions. The election of regional in Indonesia has not reached the objectives of the General Election as referred to in the Constitution 1945. This is much influenced by political parties, therefore the issue raised is the political influence in the system of regional elections. Based on the results of the discussion that analyzed and drawn conclusions: Political influence in the system of regional election in Indonesia has an important position (status) and role in every democratic system. The Party plays role very strategic liaison between government processes and citizens. Even the political parties that determine democracy, so it is a pillar that important to strengthened its institutionalization In any democratic political system (the degree of institutionalization). A good party system determines the functioning of the state administration system based on the principle of in a broad sense "checks and balances". In contrast, the effective functioning of the state's institutional functions in accordance with the principles of checks and balances under the constitution also greatly determines the quality of party systems and the mechanisms of democracy developed in a country, so that political parties are just one of the forms of institutionalization as a form of expression of ideas , Free thoughts, views, and beliefs in democratic societies and political parties that act as intermediaries in the processes of state decision making, connecting citizens with state institutions.